The passage from bone marrow niche to bloodstream triggers the metabolic impairment in Fanconi Anemia mononuclear cells - Cappelli, Enrico (Redox Biol, 2020)
Fanconi Anemia (FA) is a disease characterized by bone marrow (BM) failure and aplastic anemia. In addition to a defective DNA repair system, other mechanisms are involved in its pathogenesis, such as defective mitochondrial metabolism, accumulation of lipids, and increment of oxidative stress production. To better understand the role of these metabolic alterations in the process of HSC maturation in FA, we evaluated several biochemical and cellular parameters on mononuclear cells isolated from the bone marrow of FA patients or healthy donors. To mimic the cellular residence in the BM niche or their exit from the BM niche to the bloodstream, cells have been grown in hypoxic or normoxic conditions, respectively. The data show that, in normoxic conditions, a switch from anaerobic to aerobic metabolism occurs both in healthy and in pathological samples. However, in FA cells this change is associated with altered oxidative phosphorylation, the increment of oxidative stress production, no activation of the endogenous antioxidant defenses and arrest in the G2M phase of the cell cycle. By contrast, FA cells grown in hypoxic conditions do not show cell cycle and metabolic alterations in comparison to the healthy control, maintaining both an anaerobic flux. The data reported herein suggests that the passage from the BM niche to the bloodstream represents a crucial point in the FA pathogenesis associated with mitochondrial dysfunction.